Influence of physico-chemical properties of hydroxypropyl methylcellulose on quetiapine fumarate release from sustained release matrix tablets - Takwa E. Ellakwa; Ahmad S. Abu-Khadra; Doha El-Sayed Ellakwa (BMC Chemistry)
Abstract Quetiapine fumarateis a typical antipsychotic with a short half-life of 6 h and is administered multiple times daily. In this study, a copolymer for controlled delivery of quetiapine fumarate will be developed. In order to prevent side effects and improve patient compliance, hydroxypropyl methylcellulose K15M (HPMC K15M) was included in the formulation of the quetiapine fumarate oral sustained-release tablets at a concentration of 10–30%. A series of analytical methods were used to determine the characteristics of the prepared hydrogels, including Fourier transform-infrared spectroscopy, Differential scanning calorimetry, X-ray diffraction, and Scanning electron microscope. At two different pH values (1.2 and 6.8), swelling and release studies were conducted. A variety of release kinetic models was used to study drug release mechanisms. A non-Fickian diffusion mechanism released hydrogels prepared from quetiapine fumarate. It was found that swelling was increased by increasing the amount of HPMC K15M. Compared to the other batches (10–20%), the produced tablets with 30% HPMC K15M content had a better release profile after 20 h of dissolution. Because of the effective matrix complex’s limited solubility in water, the drug diffuses through the gel layer at a steady rate rather than dissolving quickly.